ANALISIS PENGARUH RASIO CAMEL TERHADAP KINERJA KEUANGAN - B11108153, Nopa (Jurnal Manajemen Update, 2012)
Bank is a financial institution is a place for companies, government agencies, and private sector and individuals to save funds. The basis of a bank is trust, without confidence in the banking and vice versa without the confidence of the banking community, the activities of banks will not go well, so expect the bank to have a good financial performance, due to good financial performance bank guarantee to be able to continue survive and thrive in an increasingly competitive environment sharply. The purpose of this study was to determine the effect of the ratio of the CAMEL (Capital, Assets, Management, Earning, and Liquidity) on bank performance. Object of study is a bank listed on the Stock Exchange from 2006 to 2010 the period of December 31. Samples used in this study amounted to 7 banks and the analytical technique used is multiple regression analysis (t test and F test). Based on t test results concluded that the Capital Adequacy Ratio (CAR), non-performing loans (NPLs), Net Interest Margin (NIM), Loan To Deposit Ratio (LDR), and Operating Costs Operating Revenues over (BOPO) the partial effect of the Return On assets (ROA). From the test results obtained F calculated F value of 7.046 with a P value of 0.000. This means that the P value of less than 0.05 which indicates that the variable Capital Adequacy Ratio (CAR), non-performing loans (NPLs), Net Interest Margin (NPM), compared Operating Costs Operating Income (BOPO), and the Loan to Deposit Ratio (LDR) jointly have a significant influence on Return On Asset (ROA) Keywords: CAMEL ratios, Bank Performance